Maternal vitamin D supplementation during pregnancy. Issue 1 (19th April 2018) - Curtis, Elizabeth M; Moon, Rebecca J; Harvey, Nicholas C; Cooper, Cyrus
Abstract: Introduction: Maternal vitamin D status in pregnancy has been linked to many health outcomes in mother and offspring. A wealth of observational studies have reported on both obstetric outcomes and complications, including pre-eclampsia, gestational diabetes, mode and timing of delivery. Many foetal and childhood outcomes are also linked to vitamin D status, including measures of foetal size, body composition and skeletal mineralization, in addition to later childhood outcomes, such as asthma. Sources of data: Synthesis of systematic and narrative reviews. Areas of agreement and controversy: The findings are generally inconsistent in most areas, and, at present, there is a lack of data from high-quality intervention studies to confirm a causal role for vitamin D in these outcomes. In most areas, the evidence tends towards maternal vitamin D being of overall benefit, but often does not reach statistical significance in meta-analyses. Growing points and areas timely for developing research: The most conclusive evidence is in the role of maternal vitamin D supplementation in the prevention of neonatal hypocalcaemia; as a consequence the UK department of health recommends that pregnant women take 400 IU vitamin D daily. High-quality randomized placebo-controlled trials, such as the UK-based MAVIDOS trial, will inform the potential efficacy and safety of vitamin D supplementation in pregnancy across a variety of outcomes.